Studi Peningkatan Peluang Bisnis Clean Handband Dalam Upaya Penjangkauan Pasar Yang Lebih Luas Di Universitas Negeri Medan 2026 - Mahlum Binnio Simanungkalit; Azka Tria Fatikah Siregar; Grace Romauli Sihotang; Ridho Pramana Putra Sinambela; Surya Cakra Manggala; Daffa Satria Nasution; Nadilla Sahnaz; Agustin Sastrawan Harahap; Nur Kholilah Harahap (Jurnal Ekonomi dan Bisnis Digital, 2026)
In an era of increasing emphasis on practicality and hygiene, the need for effective and easily accessible hand sanitizer continues to grow. However, the use of cloth and clothing towels and body wipes is often considered impractical, easily left behind, requiring large storage space, or lacking aesthetic appeal. This business opportunity presents Clean Handband, an innovative wristband product integrated with a safe and hygienic hand sanitizer storage and dispensing system. This product combines the dual function of being a stylish fashion accessory and a functional hygiene protection tool. Clean Handband is designed with comfortable, water-absorbent material and comes in a variety of designs that can be adapted to market trends, from casual to formal styles. The target market includes a wide range of people, from style-conscious young people and professional workers to families who prioritize simple and practical hygiene. Market analysis indicates significant growth potential as this product fills the gap between health needs and modern lifestyles. Clean Handband's competitive advantages lie in its practicality (easy to carry anywhere), attractive design, and affordable price. The marketing strategy will focus on digital platforms and collaborations with influencers, as well as custom product offerings for corporate promotions or specific events. With relatively measurable production capital and promising profit margins, the Clean Handband business is projected to have bright and sustainable prospects in the health and lifestyle products industry.